Preparation method and application of magnesium alloy surface micro-arc oxidation film-ZnPA G / LDH composite film
By constructing a ZnPA@G/LDH composite film on the surface of magnesium alloy micro-arc oxidation film, the problems of micropores and cracks in traditional magnesium alloy micro-arc oxidation film layers are solved, achieving long-term corrosion inhibition and self-repair functions, and improving the protective performance and stability of magnesium alloy.
Patent Information
- Application Number
- CN202510731802.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-03
- Publication Date
- 2025-10-24
AI Technical Summary
Traditional magnesium alloy micro-arc oxidation films have micropores and cracks, which cannot provide long-term corrosion protection in corrosive environments. They also have poor stability, low corrosion inhibitor utilization, and insufficient self-healing ability.
By employing ZnPA corrosion inhibitor and graphene/LDH composite structure, a multifunctional ZnPA@G/LDH protection system is constructed on the surface of micro-arc oxidation film. The two-dimensional sheets of graphene and LDH are vertically grown to form a three-dimensional network, which blocks the penetration path of corrosive media and achieves self-repair through the controlled release of ZnPA.
It significantly improves the density and corrosion resistance of magnesium alloy surfaces, achieves self-healing function, enhances the adhesion between the film and the substrate, avoids protective failure caused by the initial release of corrosion inhibitors, and improves the stability of magnesium alloys in harsh environments.
Smart Images

Figure CN120830108A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of metal surface protection treatment, and particularly relates to a preparation method of a magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film and application thereof. The composite film significantly improves the compactness and corrosion resistance of the magnesium alloy micro-arc oxidation film layer through the synergistic effect of a zinc-based organic corrosion inhibitor (ZnPA) and graphene (G) / layered double hydroxide (LDH), and simultaneously endows the film layer with a self-repairing function, effectively solving the problem that the porous structure of the traditional micro-arc oxidation film is easily eroded by a corrosive medium, and providing technical support for long-term stable application of the magnesium alloy in harsh environments. BACKGROUND
[0002] Magnesium alloy is known as the "green engineering material in the 21st century" due to its low density (about 1.8 g / cm 3 ), high specific strength, excellent electromagnetic shielding property and recyclability, and has shown broad application prospects in the fields of aerospace, new energy vehicles, 3C electronics, etc. However, the standard electrode potential of the magnesium alloy is extremely low (-2.37 V vs. SHE), and the chemical activity is extremely high, so the magnesium alloy is extremely prone to pitting corrosion, intergranular corrosion and stress corrosion cracking in a humid, chlorine ion-containing or other corrosive environment, which seriously restricts its large-scale engineering application.
[0003] At present, the corrosion protection research on magnesium alloy mainly focuses on two strategies: one is to optimize the corrosion resistance of the substrate through alloying or purification process, such as reducing the impurity content of Fe, Ni, etc. or introducing rare earth elements; the other is to construct a protective barrier by surface modification technology, including chemical conversion film, anodic oxidation, micro-arc oxidation (MAO), etc. Among them, the micro-arc oxidation technology can significantly improve the surface hardness, wear resistance and corrosion resistance by growing a ceramic oxidation film on the surface of the magnesium alloy in situ, and has become one of the mainstream technologies for surface treatment of magnesium alloy. However, the traditional micro-arc oxidation film is composed of a porous outer layer and a dense inner layer, and the outer layer micropores (pore size 1-10 μm) and microcracks are easily penetrated by corrosive media (such as Cl - , H2O) during service. Once the corrosive medium breaks through the outer barrier and invades the substrate interface, it will cause local peeling of the film layer, resulting in a sharp degradation of the protective performance.
[0004] To improve the long-term protective effect of micro-arc oxidation film, researchers have proposed post-treatment sealing technology, such as sol-gel sealing, hydrothermal deposition of layered double hydroxide (LDH), etc. LDH, due to its unique layered structure, ion exchange ability and corrosion inhibitor loading characteristics, can fill micropores through vertically grown nanosheets, extending the diffusion path of corrosive media. However, the single LDH film layer still has the following limitations: (1) the nanosheet orientation is single, and through cracks are easily formed; (2) the loading capacity of corrosion inhibitor is limited, and the self-repairing efficiency is low; (3) the adhesion between the LDH layer and the substrate is insufficient during long-term service, and peeling off easily. In recent years, graphene (G) has been introduced into the composite film layer design due to its ultra-high specific surface area, chemical stability and barrier properties. By combining graphene with LDH, a multi-dimensional network structure can be constructed to further improve the compactness of the film layer; at the same time, the abundant functional groups on the surface of graphene provide an ideal carrier for corrosion inhibitor anchoring.
[0005] Zinc-based organic compounds such as zinc phytate and ZnPA can form protective complexes by coordination with magnesium substrates, effectively inhibiting localized corrosion. However, direct addition of corrosion inhibitors can lead to initial "burst release", reducing long-term protection performance. Therefore, how to efficiently load ZnPA into the graphene / LDH composite carrier and achieve controlled release of corrosion inhibitors is a key to breaking through the existing technical bottlenecks.
[0006] In summary, it is of great significance to develop a micro-arc oxidation composite film layer with compact sealing, long-term corrosion inhibition and self-repairing functions to promote the engineering application of magnesium alloys in harsh environments. The present invention innovatively combines ZnPA corrosion inhibitor with graphene / LDH composite structure to construct a ZnPA@G / LDH multifunctional protection system on the surface of micro-arc oxidation film, fundamentally solving the problems of high porosity of traditional film layers, low utilization rate of corrosion inhibitors and insufficient self-repairing ability. SUMMARY
[0007] The present invention aims to at least partially solve one of the technical problems in the related art. To this end, the main purpose of the present invention is to provide a preparation method of a magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film, which aims to solve the problems of existing magnesium alloy micro-arc oxidation film layer, such as micropores and cracks, inability to provide long-term corrosion protection in corrosive environments, poor stability and other problems. The present invention also provides the application of the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film.
[0008] The purpose of the present invention is achieved by the following technical solutions:
[0009] In a first aspect, a preparation method of a magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film is provided, comprising the following steps:
[0010] A1) first prepare a micro-arc oxidation film layer on the surface of the magnesium alloy;
[0011] A2) in-situ growth of ZnPA@G / LDH film on the surface of the magnesium alloy after micro-arc oxidation;
[0012] A3) repeat cleaning of the magnesium alloy film layer after in-situ growth reaction in step A2 for 2-5 times, and dry overnight.
[0013] In some specific embodiments, in step A2, the in-situ growth specifically includes the following steps:
[0014] A21) placing the magnesium alloy after micro-arc oxidation into a GO solution prepared by adjusting 0.1-2.0 mol / L sodium nitrate to 0.01-0.5 mg / mL for in-situ growth, to obtain a magnesium alloy with a micro-arc oxidation film-G / LDH film layer on the surface;
[0015] A22) mixing and stirring 0.001-0.05 mol / L Zn(NO3)2·6H2O and 1.0-1.5 mol / L dimethyl imidazole aqueous solution, and then in-situ growing with the magnesium alloy with a micro-arc oxidation film-G / LDH film layer on the surface to obtain a magnesium alloy with a micro-arc oxidation film-ZG / LDH film layer on the surface;
[0016] A23) then mixing and stirring 0.05-0.1 mol / L ZnPA solution and 0.1-1.0 mol / L dimethyl imidazole aqueous solution after ultrasonic treatment, and then in-situ growing with the magnesium alloy with a micro-arc oxidation film-ZG / LDH film layer on the surface to obtain a magnesium alloy with a micro-arc oxidation film-ZnPA@G / LDH film layer on the surface;
[0017] In some specific embodiments, the bath solution for preparing the micro-arc oxidation film layer in step A1) includes sodium metaaluminate and sodium hydroxide, wherein the mass / volume concentration of the sodium metaaluminate is 3-6 g / L, and the mass / volume concentration of the sodium hydroxide is 6-10 g / L.
[0018] In some specific embodiments, the method for preparing the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film; the concentration of the sodium nitrate solution used for preparation is 0.5-1.5 mol / L; and the concentration of the GO solution is 0.05-0.2 mg / mL.
[0019] In some specific embodiments, the preparation method of the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film, the concentration of Zn(NO3)2·6H2O is 0.01-0.03 mol / L; the concentration of the dimethyl imidazole aqueous solution for preparing the micro-arc oxidation film-ZG / LDH film layer is 1.1-1.3 mol / L; the concentration of the dimethyl imidazole aqueous solution for preparing the micro-arc oxidation film-ZnPA@G / LDH film layer is 0.5-0.6 mol / L; and the concentration of the ZnPA solution is 0.08-0.09 mol / L.
[0020] In some specific embodiments, the preparation method of the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film, in step A21), the in-situ growth process conditions of the magnesium alloy with the micro-arc oxidation film-G / LDH film layer are as follows: the reaction temperature is 125℃, the pH is 10-11, and the reaction time is 10-15 h.
[0021] In some specific embodiments, the preparation method of the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film, in step A22), the in-situ growth process conditions are as follows: the growth temperature is room temperature, and the reaction time is 20-30 h; and in step A23), the in-situ growth process conditions are as follows: the growth environment is room temperature, and the reaction time is 20-30 h.
[0022] In some specific embodiments, the preparation method of the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film, in step A3), the cleaning is performed under the condition of ultrasonic waves by using ethanol and deionized water; and the drying condition is 40-80℃ drying in a blast drying oven for 12 h.
[0023] In the second aspect, the application relates to an application of the preparation method of the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film in magnesium alloy surface treatment.
[0024] The product obtained by the preparation method of the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film is applied in the fields of aviation, automobiles, electronic communication, etc.
[0025] Compared with the prior art, the application has at least the following advantages:
[0026] 1) The preparation method provided by the application adopts graphene oxide (GO) with rich oxygen-containing functional groups on the surface, high specific surface area and mechanical properties, which is a good carrier for loading organic corrosion inhibitors. Through the interweaving of the two-dimensional sheet structure of graphene and the vertically grown nanosheet of LDH to form a three-dimensional network, the porous structure of the micro-arc oxidation film is effectively filled, and the penetration path of the corrosion medium is blocked; at the same time, ZnPA is anchored on the surface of graphene through π-π conjugation and coordination bond, and gradually releases Zn 2+ in response to pH changes in the corrosion environment, forms a passivation film with organic corrosion inhibitor groups to inhibit local corrosion and avoid the failure of protection caused by the initial burst release of corrosion inhibitors
[0027] 2) The preparation method of the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film provided by the application utilizes the fact that when the film layer is damaged, the LDH layer adsorbs the corrosion products in the environment through ion exchange, dynamically repairing micro-cracks; at the same time, the corrosion components released by ZnPA preferentially deposit in the damaged area, realizing a double self-healing mechanism; the high specific surface area and oxygen-containing functional groups of graphene form chemical bonding with the LDH nanosheet, enhancing the bonding force between the composite film layer and the micro-arc oxidation substrate and avoiding peeling problems during service. Therefore, the preparation method fundamentally realizes the surface protection performance and self-repairing performance of magnesium alloy, and the process preparation process is simple, the operation mode is convenient, and it has the characteristics of environmental friendliness, safety and greenness, and is a safe, green and corrosion-resistant preparation process for enhancing the micro-arc oxidation film layer of magnesium alloy;
[0028] 3) The magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film obtained by the application can be widely applied in the fields of aviation, automobiles, electronic communications, etc. BRIEF DESCRIPTION OF DRAWINGS
[0029] In order to more clearly illustrate the specific embodiments of the application, the following will briefly introduce the drawings needed to be used in the specific embodiments or prior art description.
[0030] Figure 1 is the scanning electron microscope photograph of the micro-arc oxidation film layer of the magnesium alloy micro-arc oxidation surface obtained in Example 1;
[0031] Figure 2 is the scanning electron microscope photograph of the LDH film layer on the surface of the magnesium alloy micro-arc oxidation film obtained in Example 2;
[0032] Figure 3 is the scanning electron microscope photograph of the G / LDH film layer on the surface of the magnesium alloy micro-arc oxidation film obtained in Example 3;
[0033] Figure 4The XPS spectra of the surface of the magnesium alloy micro-arc oxidation film obtained in Example 1, the LDH film layer on the surface of the magnesium alloy micro-arc oxidation film obtained in Example 2, and the G / LDH film layer on the surface of the magnesium alloy micro-arc oxidation film obtained in Example 3;
[0034] Figure 5 This is a scanning electron microscope photograph of the ZG / LDH composite film layer on the surface of the magnesium alloy micro-arc oxidation film obtained in Example 4;
[0035] Figure 6 This is a scanning electron microscope photograph of the micro-arc oxidation film-ZnPA@G / LDH composite film layer on the magnesium alloy surface obtained in Example 5;
[0036] Figure 7 The XRD patterns of the MAO film, LDH film, G / LDH film, ZG / LDH film, and ZnPA@G / LDH film obtained in Example 5 with a horizontal coordinate 2θ of 5-90° are shown;
[0037] Figure 8 The XRD patterns of the MAO film, LDH film, G / LDH film, ZG / LDH film, and ZnPA@G / LDH film obtained in Example 5 with a horizontal coordinate 2θ of 5-25° are shown;
[0038] Figure 9 2p XPS spectra of the ZG / LDH film and the ZnPA@G / LDH film obtained in Example 5;
[0039] Figure 10 is the P 2p XPS spectrum of the ZnPA@G / LDH film obtained in Example 5;
[0040] Figure 11 The impedance spectra of the micro-arc oxidation film, LDH film, G / LDH film, ZG / LDH film, and ZnPA@G / LDH film after immersion in 3.5 wt % NaCl solution for 7 days, measured by an electrochemical workstation in Example 5, include the Bode spectrum (left) and Phase spectrum (right);
[0041] Figure 12 These are the impedance spectra of the micro-arc oxidation film, LDH film, G / LDH film, ZG / LDH film and ZnPA@G / LDH after immersion in 3.5wt% NaCl solution for 14 days, measured by an electrochemical workstation in Example 5, including the Bode spectrum (left) and Phase spectrum (right). DETAILED DESCRIPTION
[0042] The present invention will be further described in detail below with reference to the accompanying drawings and examples. The following examples are merely illustrative and non-restrictive, and should not be used to limit the scope of protection of the present invention.
[0043] When a range, preferably a range, or a preferred upper and lower limit of a numerical value is expressed in the form of a certain amount, concentration or other value or parameter, it is understood that any range consisting of the combination of any pair of range upper limit or preferred numerical value with any range lower limit or preferred numerical value is specifically disclosed, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical value ranges listed herein include the endpoints of the range, and all integers and fractions within the range.
[0044] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0045] The materials, methods, and examples herein are illustrative only and, unless expressly stated otherwise, are not to be construed as limiting.
[0046] Unless otherwise specified, the experimental methods in the examples are generally carried out according to conventional conditions or according to the conditions recommended by the manufacturer.
[0047] Example 1
[0048] A method for preparing a magnesium alloy surface MAO film layer, the specific steps are:
[0049] 1) Micro-arc oxidation
[0050] Micro-arc oxidation bath: according to the configuration of the bath solution of sodium hydroxide 7.14 g / L, sodium aluminate 4 g / L;
[0051] Micro-arc oxidation step: square pulse AC power as micro-arc oxidation power, magnesium alloy (take AZ31 magnesium alloy as an example) AZ31 as working electrode, stainless steel plate as cathode, use condensation circulation system to maintain the temperature of micro-arc oxidation bath at 25±5℃ all the time, working time is 5 min, pulse width is 100 μs, frequency is 500 Hz. After work, take out the magnesium alloy sample, wash back and forth with deionized water and alcohol, and dry the surface with a hair dryer. Figure 1 is the scanning electron microscope photo of the surface of the magnesium alloy after micro-arc oxidation, from Figure 1 It can be seen that the surface morphology of the magnesium alloy AZ31 micro-arc oxidation film layer obtained in Example 1 presents many holes and protrusions of different sizes, forming a porous and rough surface morphology. The micro-arc oxidation film layer (MAO layer) has strong adhesion and high stability.
[0052] Example 2
[0053] A method for preparing a magnesium alloy micro-arc oxidation film surface LDH film layer, the specific steps are:
[0054] 1) Micro-arc oxidation
[0055] The micro-arc oxidation of step 1) is the same as that of Example 1;
[0056] 2) In-situ growth of LDH film layer
[0057] A NaNO3 solution with a concentration of 1 mol / L was prepared, and a 3.0 mol / L NaOH solution was used to adjust the pH value to 10.8. The magnesium alloy with the MAO film layer (magnesium alloy AZ31 with the micro-arc oxidation film layer obtained by the preparation method of Example 1) and the NaNO3 solution were placed in a reaction kettle, the reaction kettle was tightly sealed, and finally placed in a blast drying oven for in-situ growth. The reaction temperature was 418 K, and the constant temperature time was set to 12 h. Figure 2 is a scanning electron microscope image of the magnesium alloy LDH film layer obtained in Example 2; from Figure 2 It can be seen that the LDH film layer on the surface of the magnesium alloy AZ31 micro-arc oxidation film obtained in this Example 2 shows a morphology of thin slices perpendicular to the substrate growth, which is due to the rapid accumulation of metal ions and hydrated oxide ions along a certain direction during crystal growth.
[0058] 3) Cleaning and drying
[0059] The magnesium alloy prepared in step 2) was first washed with deionized water to clean the film layer surface, then placed in anhydrous ethanol, and ultrasonically cleaned in an ultrasonic cleaner for 10 min to remove the surface residues. Then, the sample was washed with deionized water and dried with a hair dryer. The sample was stored in a dry environment and further used for morphology and structure detection.
[0060] Example 3
[0061] A method for preparing a G / LDH film layer on the surface of a magnesium alloy micro-arc oxidation film, comprising the following steps:
[0062] 1) Micro-arc oxidation
[0063] The micro-arc oxidation of step 1) is the same as that of Example 1;
[0064] 2) In-situ growth of G / LDH film layer
[0065] Firstly, the GO solution was prepared: phosphorus pentoxide (5 g) and potassium persulfate (5 g) were dissolved in concentrated sulfuric acid (25 mL) at 80°C; graphite powder (6 g) was added, stirred for 4.5 h, cooled to room temperature, the solution was diluted with deionized water (1 L) and placed overnight, filtered, washed with water (0.5 L) and dried, then added to a concentrated sulfuric acid (230 mL) solution and added KMnO4(30 g); the temperature of the solution was kept below 5°C throughout the reaction; then, cooled in an ice bath and diluted with dihydrate; after stirring for 4 h, deionized water (1.4 L) and H2O2 solution (30%, 25 mL) were added again; filtered, the pH of the suspension was adjusted to 6 with 10% hydrochloric acid (2.5 L); a GO solution with a concentration of 5 mg / mL was obtained;
[0066] A NaNO3 solution with a concentration of 1 mol / L was prepared, the GO solution was diluted to 0.1 mg / mL with the NaNO3 solution, and then a 3.0 mol / L NaOH solution was used to adjust the pH value to 10.8; the magnesium alloy with a MAO film layer (magnesium alloy AZ31 with a micro-arc oxidation film layer obtained by the preparation method of Example 1) and the NaNO3 solution were placed in a reaction kettle, the reaction kettle was tightly sealed, and finally placed in a blast drying oven for in-situ growth, the reaction temperature was 418 K, and the constant temperature time was set to 12 h. Figure 3 is a scanning electron microscope photograph of the magnesium alloy G / LDH closed film layer obtained in Example 3;
[0067] In Example 3, the magnesium alloy micro-oxidation film was subjected to a hydrothermal reaction in a GO solution, and the nanosheets of the obtained G / LDH composite film layer showed a tendency to grow in different directions; due to the amorphous nanosheet structure of GO, the G / LDH composite nanosheets showed a corrugated and edge curling shape, which was in contrast to the surface morphology of Example 2, and changed the traditional state of LDH growing perpendicular to the substrate.
[0068] 3) washing and drying
[0069] In step 2), the prepared magnesium alloy was first rinsed with deionized water, then placed in anhydrous ethanol, and ultrasonically cleaned in an ultrasonic cleaner for 10 min to remove surface residues; then rinsed with deionized water and dried with a hair dryer; stored in a dry environment for further morphology and structure detection.
[0070] Figure 4 is an XPS spectrum of the magnesium alloy micro-arc oxidation film G / LDH film layer obtained in Example 3, and an O-C=O peak at 288 eV can be observed for the film layer sample, which is derived from GO doping, indicating that GO has been successfully embedded in the LDH phase;
[0071] Example 4
[0072] A method for preparing a micro-arc oxidation film ZG / LDH film on a magnesium alloy surface, comprising the following steps:
[0073] 1) Micro-arc oxidation
[0074] The micro-arc oxidation in step 1) is the same as in Example 1;
[0075] 2) In situ growth of ZG / LDH film
[0076] First, the G / LDH membrane was prepared by dissolving phosphorus pentoxide (5 g) and potassium persulfate (5 g) in concentrated sulfuric acid (25 mL) at 80°C. Graphite powder (6 g) was added and stirred for 4.5 h. The mixture was cooled to room temperature, diluted with deionized water (1 L) and left overnight. The mixture was filtered, washed with water (0.5 L), and dried. The mixture was then added to concentrated sulfuric acid (230 mL) and KMnO4 (30 g) was added. The temperature of the solution was kept below 5°C throughout the reaction. The mixture was then cooled in an ice bath and diluted with dihydrate. After stirring for 4 h, deionized water (1.4 L) and H2O2 solution (30%, 25 mL) were added again. The mixture was filtered and the pH of the suspension was adjusted to 6 with 10% hydrochloric acid (2.5 L). A GO solution with a concentration of 5 mg / mL was obtained. A 1 mol / L NaNO3 solution was prepared and the GO solution was diluted to 0.1 mg / mL with the NaNO3 solution. The GO solution was then treated with 3.0 mol / L The pH value of the NaOH solution was adjusted to 10.8, and the magnesium alloy with the MAO film layer (the magnesium alloy AZ31 with the micro-arc oxidation film layer obtained by the preparation method of Example 1) and the NaNO3 solution were placed together in a reactor, and the reactor was tightened and sealed. Finally, the reactor was placed in a forced air drying oven for in situ growth. The reaction temperature was 418K, and the constant temperature time was set to 12h.
[0077] Then dissolve 0.55g of Zn(NO3)2·6H2O in 100mL of deionized water, and at the same time dissolve 11.35g of dimethylimidazole in 100mL of deionized water. Then slowly add the prepared dimethylimidazole aqueous solution into the Zn(NO3)2·6H2O aqueous solution and stir for five minutes; place the magnesium alloy sample with in-situ grown G / LDH film layer and the mixed solution at room temperature for 25h. Figure 5 3 is a scanning electron microscope photograph of the ZG / LDH closed film layer covered with the micro-arc oxidation film obtained in this embodiment.
[0078] Compared with the loose nanosheets of the G / LDH coating, the nanosheets of the ZG / LDH film obtained in Example 4 show a denser flaky structure, which increases the density of the coating and provides a great possibility for extending the invasion path of the corrosive medium.
[0079] 3) Clean and dry
[0080] The magnesium alloy prepared in step 2 is first washed with deionized water to clean the surface of the film layer, then placed in anhydrous ethanol, and ultrasonically cleaned in an ultrasonic cleaner for 10 min to remove the surface residues, then washed with deionized water, dried with a hair dryer, and stored in a dry environment for further testing of morphology, corrosion resistance, etc.
[0081] Example 5
[0082] A method for preparing a ZnPA@G / LDH self-repairing film layer on the surface of a magnesium alloy micro-arc oxidation film, the specific steps are as follows:
[0083] 1. Micro-arc oxidation
[0084] The micro-arc oxidation of step 1 is the same as that of example 1.
[0085] 2. In-situ growth of ZnPA@G / LDH film layer
[0086] First, prepare G / LDH film: dissolve phosphorus pentoxide (5 g) and potassium persulfate (5 g) in concentrated sulfuric acid (25 mL) at 80°C; add graphite powder (6 g), stir for 4.5 h, cool to room temperature, dilute the solution with deionized water (1 L) and let it stand overnight, filter, wash with water (0.5 L) and dry, then add it to a concentrated sulfuric acid (230 mL) solution and add KMnO4 (30 g); during the entire reaction process, the temperature of the solution is kept below 5°C; then, cool in an ice bath and dilute with dihydrate; after stirring for 4 h, add deionized water (1.4 L) and H2O2 solution (30%, 25 mL) again; filter, adjust the pH of the suspension to 6 with 10% hydrochloric acid (2.5 L); obtain a GO solution with a concentration of 5 mg / mL; prepare a NaNO3 solution with a concentration of 1 mol / L, dilute the GO solution to 0.1 mg / mL with the NaNO3 solution, and then adjust the pH value to 10.8 with a 3.0 mol / L NaOH solution; place the magnesium alloy with MAO film layer (magnesium alloy AZ31 with micro-arc oxidation film layer obtained by the preparation method of example 1) and the NaNO3 solution in a reaction kettle, tighten the lid, and finally place it in a forced air drying oven for in-situ growth, with a reaction temperature of 418 K and a constant temperature time of 12 h.
[0087] Dissolve 0.2 g of ZnPA in 6 mL of deionized water and ultrasonically disperse for 20 min, and at the same time, dissolve 2.84 g of dimethyl imidazole in 54 mL of deionized water and stir for 10 min; slowly add the ZnPA solution to the dimethyl imidazole solution under stirring conditions; place the magnesium alloy sample with in-situ grown G / LDH film layer in the mixed solution at room temperature for 25 h.
[0088] Figure 6is the scanning electron microscope photo of the ZnPA@G / LDH composite film layer on the surface of the magnesium alloy micro-arc oxidation film obtained in Example 5.
[0089] After the ZnPA nanoparticles are grown in situ on the surface of the G / LDH composite film layer in Example 5, the surface morphology of the film layer changes significantly, the irregular voids in the G / LDH film layer completely disappear, and the surface is uniformly covered with ZnPA, which interweaves with the LDH nanosheets to form a dense three-dimensional network structure, significantly closing the pores of the micro-arc oxidation film.
[0090] 3) washing and drying
[0091] The magnesium alloy prepared in step 2 is first washed with deionized water to clean the surface of the film layer, then placed in anhydrous ethanol, and ultrasonically cleaned in an ultrasonic cleaner for 10 min to remove the surface residues, then washed with deionized water, dried with a hair dryer, and stored in a dry environment for further testing of the morphology, corrosion resistance, self-repairing property, etc.
[0092] Figure 7 Figure 8 is the XRD pattern of the MAO film layer, the LDH film layer, the G / LDH film layer, the ZG / LDH film layer, and the ZnPA@G / LDH film layer obtained in Example 5, the composite film layer retains the (101) and (110) characteristic peaks of LDH at 37.8° and 57.4°, and the ZnPA@G / LDH film layer has a new diffraction peak at 7.3°, confirming the successful in-situ growth of the ZIF-8 crystal structure on the G / LDH film layer.
[0093] Figure 9 and Figure 10 is the XPS pattern of the MAO film layer, the LDH film layer, the G / LDH film layer, the ZG / LDH film layer, and the ZnPA@G / LDH film layer obtained in Example 5, the appearance of the Zn 2p orbital binding energy (1021.23 eV and 1044.20 eV) and the P 2p peak (133.2 eV and 139.8 eV) confirms that the Zn 2+ and the phosphate group in the ZnPA stably exist in the composite film.
[0094] Figure 11 is the impedance pattern of the MAO film layer, the LDH film layer, the G / LDH film layer, the ZG / LDH film layer, and the ZnPA@G / LDH measured by an electrochemical workstation after being immersed in a 3.5wt% NaCl solution for 7 days in Example 5; after being immersed for 7 days, the |Z| 0.01Hz of the ZnPA@G / LDH film layer reaches 3.2×10 6 Ωcm 2 , which is significantly higher than that of other film layers, indicating that the dense structure effectively blocks the penetration of corrosive media; the phase angle is 10-2 to 10 5 The maximum value in the range of 10-100 Hz is -75°, and it remains stable in the low and medium frequency region, indicating that the film layer is complete, and the corrosion medium is difficult to invade the substrate.
[0095] Figure 12 is the impedance diagram of MAO film layer, LDH film layer, G / LDH film layer, ZG / LDH film layer and ZnPA@G / LDH measured by an electrochemical workstation after being immersed in 3.5wt% NaCl solution for 14 days, and |Z| 0.01Hz The value further increases to 4.8×10 6 Ωcm 2 , indicating that when the film layer is corroded by the corrosion medium, it can respond to the corrosion area in time, release the corrosion inhibitor, make up for the surface defects, and prevent the corrosion area from spreading, and has the self-healing performance; Figure 11 and Figure 12 The phase angle curves are highly coincident, indicating that the film layer capacitance is stable, and the interface defects do not expand with time.
[0096] In addition, the phase angle of the ZnPA@G / LDH film layer at the highest frequency is always greater than that of other film layers. The |Z| 0.01Hz value of the ZnPA@G / LDH film layer always remains the highest among all samples, indicating that the film layer has good compactness and optimal protection performance.
[0097] The inventors found through a large number of experimental researches that the ZnPA@G / LDH film layer is prepared on the surface of the magnesium alloy micro-arc oxidation film, the porous film layer is generated on the surface of the magnesium alloy by micro-arc oxidation, the LDH nanosheet is then vertically grown in the MAO pores by using one-step hydrothermal method, the GO and the LDH vertical nanosheet are interwoven to form a dense three-dimensional structure, the pores are further closed, the dimethyl imidazole is coordinated with Zn 2+ to form an organic framework to enhance the film layer binding force, and finally the ZnPA is anchored on the surface of the G / LDH through π-π interaction, and the dimethyl imidazole promotes the uniform dispersion, and the construction of the ZnPA@G / LDH film layer on the surface of the magnesium alloy micro-arc oxidation film is successfully realized. The LDH interlayer adsorbs Cl - and other corrosive ions, reduces the substrate corrosion through ion exchange, and the high conductivity of GO promotes electron transfer and inhibits local galvanic corrosion. In addition, the doping of zinc makes Zn 2+ preferentially corrode through displacement reaction, and form a Zn(OH)2passivation film to further protect the substrate, and the ZnPA releases Zn 2+ and phosphate when the pH of the corrosion micro-area increases, can respond to the corrosion area, make up for the damaged area, and form a dense phosphoric acid passivation film with self-healing effect.
[0098] The above examples are only used to illustrate the technical solutions of the present application, but not limit the present application; although the present application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that the technical solutions recorded in the foregoing examples can be modified, or some or all of the technical features can be replaced equivalently; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should be covered in the scope of the claims and the specification of the present application.
Claims
1. A method for preparing a magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film, characterized in that, Comprising the following steps: A1) Constructing a porous oxide film on the surface of a magnesium alloy substrate as a composite substrate by micro-arc oxidation technology; A2) Constructing a ZnPA@G / LDH composite film layer on the surface of the micro-arc oxidation film by in-situ growth process, wherein the directional growth of the LDH film layer and the stable embedding of the ZnPA@G nano material are ensured by adjusting the pH value and hydrothermal conditions of the reaction system; A3) Gradient cleaning of the composite film layer in step A2) to remove loose attachments, followed by vacuum drying overnight to form a dense film structure.
2. The method for preparing the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film according to claim 1, characterized in that, In step A2), the in-situ growth specifically comprises the following steps: A21) Placing the magnesium alloy after micro-arc oxidation into a GO solution prepared by 0.1-2.0mol / L sodium nitrate to 0.01-0.5mg / mL for in-situ growth, to obtain a magnesium alloy with a micro-arc oxidation film-G / LDH film layer on the surface; A22) Mixing and stirring 0.001-0.05mol / L Zn(NO3)2·6H2O and 1.0-1.5mol / L dimethyl imidazole aqueous solution, and then in-situ growing with the magnesium alloy with a micro-arc oxidation film-G / LDH film layer on the surface to obtain a magnesium alloy with a micro-arc oxidation film-ZG / LDH film layer on the surface; A23) Then mixing and stirring 0.05-0.1mol / L ZnPA solution and 0.1-1.0mol / L dimethyl imidazole aqueous solution after ultrasonic, and then in-situ growing with the magnesium alloy with a micro-arc oxidation film-ZG / LDH film layer on the surface to obtain a magnesium alloy with a micro-arc oxidation film-ZnPA@G / LDH film layer on the surface.
3. The method for preparing the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film according to claim 1, characterized in that, In step A1), the bath solution for preparing the micro-arc oxidation film layer comprises sodium metaaluminate and sodium hydroxide, wherein the mass / volume concentration of the sodium metaaluminate is 3-6g / L, and the mass / volume concentration of the sodium hydroxide is 6-10g / L.
4. The method for preparing the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film according to claim 2, characterized in that, The concentration of the sodium nitrate solution used for the preparation is 0.5-1.5mol / L; the concentration of the GO solution is 0.05-0.2mg / mL.
5. The method for preparing the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film according to claim 2, characterized in that, The concentration of the Zn(NO3)2·6H2O is 0.01-0.03mol / L, the concentration of the dimethyl imidazole aqueous solution for preparing the magnesium alloy with a micro-arc oxidation film-ZG / LDH film layer is 1.1-1.3mol / L, the concentration of the dimethyl imidazole aqueous solution for preparing the magnesium alloy with a micro-arc oxidation film-ZnPA@G / LDH film layer is 0.5-0.6mol / L, and the concentration of the ZnPA solution is 0.08-0.09mol / L.
6. The method for preparing the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film according to claim 5, characterized in that, In step A21), the process conditions for in-situ growth of the magnesium alloy with a micro-arc oxidation film-G / LDH film layer are as follows: the reaction temperature is 125℃, the pH is 10-11, and the reaction time is 10-15h.
7. The method according to claim 6, wherein the method comprises the following steps: 1) preparing a magnesium alloy surface micro-arc oxidation film; 2) preparing a ZnPA@G / LDH composite film on the magnesium alloy surface micro-arc oxidation film. In step A22), the process conditions for in-situ growth are as follows: the growth temperature is room temperature, and the reaction time is 20-30h; in step A23), the process conditions for in-situ growth are as follows: the growth environment is room temperature, and the reaction time is 20-30h.
8. The method for preparing the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film according to claim 1, characterized in that, In step A3), the cleaning is performed using ethanol and deionized water under the condition of ultrasonic wave; the drying condition is 40-80℃ drying in a blast drying oven for 12h.
9. The application of the preparation method of the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film according to any one of claims 1-8 in the surface treatment of magnesium alloys.
10. The application of the product obtained by the preparation method of the magnesium alloy surface micro-arc oxidation film-ZnPA@G / LDH composite film according to any one of claims 1-8 in the fields of aviation, automobiles and electronic communications.